Freedom of association and collective bargaining (ILO GenevaCH, 1994)
Deals with Freedom of Association and Protection of the Right to Organize Convention; the right to Organize and Collective Bargaining Convention; and highlights of the last decade and the difficulties and prospects with regard to ratification.
DC